Limited genetic variations of the Rh5-CyRPA-Ripr invasion complex in Plasmodium falciparum parasite population in selected malaria-endemic regions, Kenya - Waweru, Harrison; Kanoi, Bernard N.; Kuja, Josiah O.; Maranga, Mary; Kongere, James; Maina, Michael; Kinyua, Johnson; Gitaka, Jesse (Frontiers in Tropical Diseases, 2023)
The invasion of human erythrocytes by Plasmodium falciparum merozoites requires interaction between parasite ligands and host receptors. Interaction of PfRh5-CyRPA-Ripr protein complex with basigin, an erythrocyte surface receptor, via PfRh5 is essential for erythrocyte invasion. Antibodies raised against each antigen component of the complex have demonstrated erythrocyte invasion inhibition, making these proteins potential blood-stage vaccine candidates. Genetic polymorphisms present a significant challenge in developing efficacious vaccines, leading to variant-specific immune responses. This study investigated the genetic variations of the PfRh5 complex proteins in P. falciparum isolates from Lake Victoria islands, Western Kenya. Here, twenty-nine microscopically confirmed P. falciparum field samples collected from islands in Lake Victoria between July 2014 and July 2016 were genotyped by whole genome sequencing, and results compared to sequences mined from the GenBank database, from a study conducted in Kilifi, as well as other sequences from the MalariaGEN repository. We analyzed the frequency of polymorphisms in the PfRh5 protein complex proteins, PfRh5, PfCyRPA, PfRipr, and PfP113, and their location mapped on the 3D protein complex structure. We identified a total of 58 variants in the PfRh5 protein complex. PfRh5 protein was the most polymorphic with 30 SNPs, while PfCyRPA was relatively conserved with 3 SNPs. The minor allele frequency of the SNPs ranged between 1.9% and 21.2%. Ten high-frequency alleles (>5%) were observed in PfRh5 at codons 147, 148, 277, 410, and 429 and in PfRipr at codons 190, 255, 259, and 1003. A SNP was located in protein-protein interaction region C203Y and F292V of PfRh5 and PfCyRPA, respectively. Put together, this study revealed low polymorphisms in the PfRh5 invasion complex in the Lake Victoria parasite population. However, the two mutations identified on the protein interaction regions prompts for investigation on their impacts on parasite invasion process to support the consideration of PfRh5 components as potential malaria vaccine candidates.